(untitled) (Journal of Libya for geographical studies, 2025)
This study aims to identify the small projects in the municipality of Misrata and their role in achieving economic development through their impact on the local economy of the area by providing job opportunities and improving individual income levels. It also seeks to highlight the main geographical factors affecting the success of these projects and the key challenges they face. This was done through a questionnaire consisting of six sections distributed to a purposive (non-probabilistic) sample of 150 projects in the area. The results showed a moderate impact of small projects on the local economy, influenced by several factors and challenges related to the geographical location of the projects, infrastructure, financing, and the local market. Various statistical methods were used to test the study’s hypotheses, such as the arithmetic mean, standard deviation, and correlation coefficient.